The perfect human capital storm : workplace human capital challenges and opportunities in the 21st century implications for organizations and leaders - Mouriño-Ruiz, Edwin (Emerald Publishing Limited : Information Age Publishing Inc., 2017)
There are numerous trends taking place around the world and especially in the U.S. with implications for organizations, the workplace, leaders, and supporting organizations like Human Resources. How organizations and their leadership react and proactively address these changes will be difference between positioning themselves for success in the future or for disappearing as other organizations have disappeared.The critically important issue of these trends is that they are occurring simultaneously. The trends consists of constant and consistent change driven by advancing technology, challenges with education with implications for a future workforce, an aging population and workforce, four generations in the workforce with a growing millennial workforce, changing expectations from the workforce with an emphasis on employee engagement, and leadership development opportunities.This perfect human capital storm addresses these very important and relevant issues in a succinct fashion while also providing some systemic recommendations for organizations and its leadership to consider as they work to differentiate themselves from their competition, to look to reinvent themselves, while also creating a great place to work in the 21st century. In addition, the book provides an assessment to use as a guide and to serve as a starting point for discussion and planning among the organization's leadership team for the organization.
Keywords: Human capital -- Management.; Manpower planning.; Personnel management.; Business & Economics -- Human Resources & Personnel Management.; Organizational theory and behaviour.; Personnel and human resources management.; elektronické knihy; electronic books